OBSERVAÃ‡Ã•ES SOBRE O PARASITISMO EM OVOS ð˜—ð˜ªð˜¦ð˜»ð˜°ð˜¥ð˜°ð˜³ð˜¶ð˜´ ð˜¨ð˜¶ð˜ªð˜ð˜¥ð˜ªð˜¯ð˜ªð˜ª (WEST.) - Cividanes, Francisco J.; Athayde, Manoel L. F.; Sabugosa, Eduardo T. (REVISTA DE AGRICULTURA, 2020)
OBSERVAÃ‡Ã•ES SOBRE O PARASITISMO EM OVOS ð˜—ð˜ªð˜¦ð˜»ð˜°ð˜¥ð˜°ð˜³ð˜¶ð˜´ ð˜¨ð˜¶ð˜ªð˜ð˜¥ð˜ªð˜¯ð˜ªð˜ª (WEST.)